Sap Extract Papaya for Autolitic Debridement Chronic Wound - Agus Yuswanto, Tri Johan; Hariyanto, Tanto (Universitas Airlangga, 2015)
Introduction: The high cost of drugs or specific wound dressings for chronic wounds can be healed at least in two weeks depending on the stage of the wound and blood sugar levels. Hence the need for an innovative processing of natural resources (NR) to produce a chronic wound care products that are accessible to all people.Â One of the current trends is to use protease enzymes (sap extract papaya) that serves as autolitic debridement in the treatment of chronic wounds. The aims of this research was to indentify characteristics of protease enzyme present in sap of papaya. Method: This study was a descriptive exploratory that doing pure protease enzyme extract of papaya sap. Results: Molecular weight measurement using a kit Pre-stained Protein Markers (Broad Range) for SDS PAGE, Nacalai tesque No. 02525 showed a homogeneous molecular weight that slightly above 28 kD. Measurements of the enzyme levels using NanoDrop Spectrophotometer ND kit-1000 (with a distilled water marker) showed a relatively homogeneous enzyme level with a range between 43% - 61% and 53, 88% in average. The addition of papaya sap extract into each tube containing 7 ml gelatin obtained results: the control group there were clots perfectly on gelatin; groups with the addition of 2 drops (Â± 0.5 ml) obtained 50% hydrolyzed gelatin; and groups with the addition of 4 drops (Â± 0.5 ml) obtained 75% hydrolyzed gelatin. Discussion: The results showed that papaya sap extraction synonymous with protease enzyme. Papaya sap extraction activity (protease enzymes) on hydrolyzing gelatin shows a qualitative picture. Therefore, it can be used as autholitic debridement. Further, the following study is essential to identify structure and activity of the enzyme with a more determinant (temperature, time, and dose).Keywords: sap papaya extraction, protease enzymes